2017
DOI: 10.1007/978-3-319-70178-3_20
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Coupled Estrogen Receptor (GPER) and Sex-Specific Metabolic Homeostasis

Abstract: Obesity and metabolic syndrome display disparate prevalence and regulation between males and females. Human, as well as rodent, females with regular menstrual/estrous cycles exhibit protection from weight gain and associated chronic diseases. These beneficial effects are predominantly attributed to the female hormone estrogen, specifically 17β-estradiol (E2). E2 exerts its actions via multiple receptors, nuclear and extranuclear estrogen receptor (ER) α and ERβ, and the G-protein-coupled estrogen receptor (GPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 180 publications
(262 reference statements)
5
57
1
Order By: Relevance
“…Pharmacological stimulation of GPER in vivo limits weight gain and improves metabolic output, revealing a promising novel therapeutic potential for the treatment of obesity and diabetes. 28 In our study, GPER was not correlated with BMI in FMS patients. It was suggested that GPER has a modulator role in energy homeostasis (weight control).…”
Section: Discussioncontrasting
confidence: 63%
“…Pharmacological stimulation of GPER in vivo limits weight gain and improves metabolic output, revealing a promising novel therapeutic potential for the treatment of obesity and diabetes. 28 In our study, GPER was not correlated with BMI in FMS patients. It was suggested that GPER has a modulator role in energy homeostasis (weight control).…”
Section: Discussioncontrasting
confidence: 63%
“…GPER1 activates multiple downstream signaling pathways, resulting in the activation of adenylate cyclase and increasing cyclic AMP levels, which promote intracellular calcium mobilization and synthesis of phosphatidylinositol 3,4,5-trisphosphate within the nucleus (16)(17)(18). GPER1 regulates a diverse range of biological processes, including bone and nervous system development, metabolism, cognition, male fertility and uterine function (19).…”
Section: The Roles Of Estrogen and Estrogen Receptors In Gastrointestmentioning
confidence: 99%
“…All these beneficial effects progressively disappear with menopause. Estrogens act through specific receptors distributed centrally and peripherally including ERα, ERβ and the G-protein-coupled receptor GPR30 which differ in abundance and tissue distribution in a sex-dependent manner [16,19,20]. Non-genomic actions of estrogens as well as cross-talk with various nuclear receptors and/or transcription factors have also been evidenced [21,22].…”
mentioning
confidence: 99%